Purple power: Unleashing the vibrant potential of red cabbage anthocyanins in functional food packaging systems - Elysa Grace Edward; Kobun Rovina; Wahidatul Husna Zuldin; Wolyna Pindi; Sylvester Mantihal; Luh Suriati; Sarifah Supri (Springer Nature, 2025)
In a world shifting toward clean labels and zero-waste living, red cabbage anthocyanins (RCAs) are stepping into the spotlight, not just as natural pigments, but as smart, bioactive heroes in sustainable packaging. Their striking hues, pH-sensitive behavior, and antioxidant power make them ideal for crafting active and intelligent food packaging systems that do more than just wrap. They protect, preserve, and communicate freshness in real time. This review unpacks the vibrant chemistry of RCAs and their seamless fusion with biopolymers and next-gen materials to create packaging that is not only biodegradable but functionally beautiful. We spotlight cutting edge green extraction methods, like ultrasound-assisted, enzyme-assisted, microwave-assisted, and supercritical fluid extraction, that boost both yield and eco-cred. This paper also explores how RCAs respond to environmental triggers like light and temperature, discusses their health concerns and toxicity, and dives into innovations like nanoencapsulation for stability and controlled release. Beyond the lab, we zoom out to consider real-world impact, which are agro-waste valorization, industrial scalability, and how RCAs align with circular economy vibes. The bottom line is that red cabbage anthocyanins are not just natural, they are powerful, purposeful, and packed with potential to reimagine food packaging for a more aesthetic, intelligent, and sustainable future.